2018
DOI: 10.1080/00423114.2017.1423091
|View full text |Cite
|
Sign up to set email alerts
|

Integrated evasive manoeuvre assist for collision mitigation with oncoming vehicles

Abstract: Citation for the published paper: Arikere, A. ; Yang, D. ; Klomp, M. et al. (2018) "Integrated evasive manoeuvre assist for collision mitigation with oncoming vehicles". Vehicle System Dynamics pp. 1-27. http://dx.doi.org/10. 1080/00423114.2017.1423091 Downloaded from: http://publications.lib.chalmers.se/publication/254461 Notice: Changes introduced as a result of publishing processes such as copy-editing and formatting may not be reflected in this document. For a definitive version of this work, please re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Arikere et al [4] developed an integrated controller that performs both longitudinal acceleration and yaw stability control. The aim is to better balance the oncoming vehicle collision risk against loss of control.…”
Section: Related Work Table I Brings a Comparison Between Previously Developed Risk Mitigation Methods And The One Presented On This Workmentioning
confidence: 99%
“…Arikere et al [4] developed an integrated controller that performs both longitudinal acceleration and yaw stability control. The aim is to better balance the oncoming vehicle collision risk against loss of control.…”
Section: Related Work Table I Brings a Comparison Between Previously Developed Risk Mitigation Methods And The One Presented On This Workmentioning
confidence: 99%
“…Work on recovering from such situations was developed in [38] and more recently in [39]. In [40] control allocation for avoidance maneuvers with oncoming vehicles is developed. There it is shown that for some combinations of obstacle length, ego vehicle and oncoming vehicle speed even acceleration may be required to minimize the collision risk.…”
Section: Automated Driving On Public Roadsmentioning
confidence: 99%
“…Finite driving behaviors sometimes seems to be conservative or have complicated switch rules to consider more feasible actions. For example, an emergency forward collision condition, despite emergency braking and emergency lane-changing with acceleration or deceleration, can be chosen in some situations [10], [11]. Meanwhile, the great uncertainty and non-linearity of drivers' behaviors can be considered [6].…”
Section: A State-of-the-art Review and Challengesmentioning
confidence: 99%
“…When longitudinal velocity changes are considered, the linear model is transformed into a nonlinear model, which can greatly increase the system complexity. Integrated longitudinal and lateral control is seldom used in trajectory planning [10]. In addition, some research employs predefined trajectory shapes (such as spine curves or polynomial curves [19]- [22]), which are closely related to tasks but lack flexibility when encountering different scenarios and changeable decisions.…”
Section: A State-of-the-art Review and Challengesmentioning
confidence: 99%